2001
DOI: 10.1063/1.1343479
|View full text |Cite
|
Sign up to set email alerts
|

Dominant role of the piezoelectric field in the pressure behavior of InGaN/GaN quantum wells

Abstract: We show that the emission characteristics of InGaN/GaN quantum wells under hydrostatic pressure are strongly influenced by the built-in piezoelectric field. The dominant role of the piezoelectric field is established from the dramatic increase of the photoluminescence decay time with pressure and the dependence of the linear pressure coefficient of the photoluminescence peak energy on Si doping in the barriers and excitation intensity. A nonlinear increase of the piezoelectric field with hydrostatic pressure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 13 publications
4
41
0
Order By: Relevance
“…The experimental results just described are quite similar to the observations made in our previous work on In x Ga 1Ϫx N/GaN QWs, 6 and provide additional evidence on the nonlinear behavior of the polarization in the III-V nitrides. As in the case of In x Ga 1Ϫx N/GaN QWs, the small values of dE/dp and their well width dependence result from an increase of the built-in electric field with pressure.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…The experimental results just described are quite similar to the observations made in our previous work on In x Ga 1Ϫx N/GaN QWs, 6 and provide additional evidence on the nonlinear behavior of the polarization in the III-V nitrides. As in the case of In x Ga 1Ϫx N/GaN QWs, the small values of dE/dp and their well width dependence result from an increase of the built-in electric field with pressure.…”
supporting
confidence: 80%
“…In agreement with this prediction, we demonstrated experimentally that the piezoelectric coefficients in In x Ga 1Ϫx N/GaN QWs significantly depend on the strain. 6 We have also suggested that volumetric as well as volume conserving components of strain affect these coefficients. Recently, Bernardini and Fiorentini investigated theoretically the effects of strain and composition on macroscopic polarization in III-V nitrides, and showed that in addition to the nonlinearity in the piezoelectric component of polarization, the spontaneous polarization is also nonlinear with respect to composition.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Also in the case of InGaN/GaN quantum wells similar behaviour was observed. [14][15][16] Generally the increase of built-in electric field is explained by pressure induced increase of strain which leads to an increase of piezoelectric component of built-in electric field. Actually the experimental observations are explained by more sophisticated theories including nonlinear piezoelectric constants, pressure-induced changes of the exciton binding energy and nonlinear elastic stiffness coefficients.…”
Section: 10mentioning
confidence: 99%